Strategic guidelines on the development of renewable energy sources - O.А. Mykoliuk; V.М. Bobrovnyk (Global Journal of Environmental Science and Management)
The study highlights the importance to develop the national economy through assuring energy security. The study aims to analyze how to develop renewable energy sources, determine the main priorities of Ukraine’s national security policy and discover novel ways of assuring energy security due to developing the industry of renewable energy in the light of environmental safety, energy conservation, and efficiency. The following scientific methods were employed: synthesis and analysis – to determine the essence and significance of RES in order to assure energy security; theoretical generalization – to single out the main stages of renewable energy development; classification – to classify the main advantages of introduction of RES, as well as the obstacles to their implementation; logical generalization – to justify the relevance, aim and objectives of the study; the method of rising from the abstract to the concrete – to develop and justify the ways of assuring energy security provided that renewable production is developed. The following results are obtained: the main conditions for developing RE are determined; some relevant issues of energy efficiency and assurance of Ukraine’s energy security are justified; significant potential of Ukraine’s renewable energy industry is discovered and analyzed; target values Ukraine seeks to achieve with the help of the energy generated from RES in final energy consumption are analyzed; the main criteria for developing Ukraine’s fuel and energy complex are revealed and the key branch ratio values of the state’s energy balance are determined.